â€œPENGARUH SUPPLY CHAIN MANAGEMENT TERHADAP KINERJA OPERASIONAL OUTLETâ€ (Studi Pada Counter Handphone yang terdaftar di PT. Multikom Indonesia Cabang Semarang) - Fitrianto, Ahmad Yudha; Sudaryanto, Budi (Faculty of Economics and Business Diponegoro University, 2016)
The competitiveness of mobile phone stores and phone deposit outlets in Semarang are not attractive enough to the writer’s opinion. Owners should know and understand the need of their consumers. They choose Supply Chain Management as a strategy to enhance outlets’ operational and performance. The strategy is also aimed to increase the competitiveness of the business in the market. The research is aimed at analysing the impact of independent variables such as Information Sharing, Long Term Relationship, Cooperation and Process Integration to the dependent variables of the outlets’ performance.The population of the research consists of 171 outlets. The samples used in the research are 120 outlets owners in Semarang. Doubled linear analysis is used on this research. The writer used SPSS 16 for Windows as data processor tool.The result of the research explains that Information Sharing positively giving no significance toward outlets’ performance. In other hand, Long Term Relationship gives positive impact and significant to the outlets’ performance. The better Long Term Relationship between a mobile phone outlet and a distributor will improve the performance of the outlets. However, Cooperation positively giving no significance toward outlets’ performance. The better Integration Process between a mobile phone outlet and a distributor will help increasing the outlets’ performance.